Post-transplant cyclophosphamide or cell selection in haploidentical allogeneic hematopoietic cell transplantation? - Razan Mohty; Zaid Al Kadhimi; Mohamed Kharfan-Dabaja (Hematology)
Background One major limitation for broader applicability of allogeneic hematopoietic cell transplantation (allo-HCT) in the past was the lack of HLA-matched histocompatible donors. Preclinical mouse studies using T-cell depleted haploidentical grafts led to an increased interest in the use of ex vivo T-cell depleted (TCD) haploidentical allo-HCT. TCD grafts through negative (T-cell depletion) or positive (CD34+ cell selection) techniques have been investigated to reduce the risk of graft-versus-host disease (GVHD) given the known implications of alloreactive T cells. A more practical approach to deplete alloreactive T cells in vivo using high doses of cyclophosphamide after allografting has proved to be feasible in overcoming the HLA barrier. Such approach has extended allo-HCT feasibility to patients for whom donors could not be found in the past. Nowadays, haploidentical donors represent a common donor source for patients in need of an allo-HCT. The broad application of haploidentical donors became possible by understanding the importance of depleting alloreactive donor T cells to facilitate engraftment and reduce incidence and severity of GVHD. These techniques involve ex vivo graft manipulation or in vivo utilization of pharmacologic agents, notably post-transplant cyclophosphamide (PTCy).Discussion While acknowledging that no randomized controlled prospective studies have been yet conducted comparing TCD versus PTCy in haploidentical allo-HCT recipients, there are two advantages that would favor the PTCy, namely ease of application and lower cost. However, emerging data on adverse events associated with PTCy including, but not limited to cardiac associated toxicities or increased incidence of post-allograft infections, and others, are important to recognize.